Study on Energy Flow in the Ecosystem: Understanding Biomass and Productivity in Diverse Ecosystems (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The world contains an extraordinary variety of ecosystems, ranging from equatorial forests to deserts and including a multitude of different vegetation types. Diversity of biomass and structure is matched by a large variation in productivity. We have some knowledge regarding the productive capacity of these ecosystems, but this knowledge is incomplete and contains a large degree of error.